Oral corrective feedback, foreign language anxiety and L2 development. (April 2015) - Rassaei, Ehsan
Abstract: Although a number of previous studies have investigated and compared the effects of different types of corrective feedback on L2 development, it is still not clear whether low- and high-anxiety learners benefit differently or similarly from implicit and explicit types of feedback. The study reported in this paper investigated the extent to which learners with high and low foreign language (FL) anxiety benefit from recasts and metalinguistic corrective feedback. To this end, 101 EFL learners were first classified into high- and low-anxiety groups according to scores they obtained in an anxiety questionnaire. Then, each anxiety group was further subdivided randomly into two treatment conditions that received either recasts or metalinguistic corrective feedback for their errors as well as one control group. Three dependent measures were also used on two occasions as pre-test and post-test to investigate the effects of corrective feedback and FL anxiety on learners' development. The results indicated that low-anxiety learners benefited from both metalinguistic feedback and recasts although the effect of metalinguistic feedback on their development was more profound. Conversely, the high-anxiety learners benefited from recasts significantly more than they did from metalinguistic corrective feedback.